ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP NIAT BERKELANJUTAN DALAM PENGGUNAAN E-WALLET SHOPEEPAY - Nike Ferani; Suhesti Ningsih; LMS Kristiyanti (CV. Denasya Smart Publisher, 2025)
This study aims to analyze the influence of perceived ease of use, financial literacy, and perceived usefulness on the continuous intention to use ShopeePay as an e-wallet in shopping activities. The research employed a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 100 active ShopeePay users in the Solo Raya region, selected using purposive sampling. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results indicate that, partially, all three variables—perceived ease of use, financial literacy, and perceived usefulness—have a positive and significant influence on the continuous intention to use ShopeePay. The Adjusted R² value of 0.437 suggests that 43.7% of the variability in continuous usage intention can be explained by the three independent variables.